Community based cross sectional study to assess the drinking water handling practices and its association with water borne diseases at household level, in a tribal community - Fernandes, Sophia D.; Chakkarwar, Priyanka (International Journal Of Community Medicine And Public Health, 2018)
Background: 71% of India resides in its villages. The living conditions in rural areas are poor, which make India’s rural population more vulnerable to inaccessibility of safe drinking water and high risk of water borne diseases. Water safety in a community depends on a range of factors, from the quality of source water to storage and handling in the domestic setting. The present study was conducted to understand the knowledge and practices about hygiene of drinking water. Methods: A community-based, cross-sectional observational study was conducted in Sakhawar a tribal village of Palghar district, Mumbai, Maharashtra, to study the water handling practices in households and its association with the prevalence of water borne diseases. One Pada was selected randomly for study. The duration of data collection was three months. All the houses in the Pada were included in the study. Results: Of the 152 households included in the study, 47.4% did not use any method of water disinfection whereas 15% used boiling and 40% used chlorination as a method of water disinfection. Tap water was the commonest source of drinking water used by 52.6% of households. Only 7.9% subjects used ladle to draw stored water. The prevalence of water borne diseases was 81.57% and was significantly associated with distance of drinking water source from house, education status, family type, duration of water supply, knowledge of water disinfection methods and water disinfection practiced. Conclusions: Health education, promotion and practice of hygienic water handling practices can significantly reduce water borne diseases morbidity.